Melhoramento do desempenho de unidades hibridas PV/BESS em microrredes através do conversor bidirecional entrelaçado de três fases com controle IMC - Lima, Lindemberg Roberto de (2023)
This research covers the theoretical study, mathematical modeling, and control design of a three-phase photovoltaic/battery generation unit in a microgrid environment, with grid follower control in connected mode and grid forming control droop for islanded mode, aiming to adopt a three-phase, non-isolated, interleaved, bi-directional current DC-DC battery converter. These converter topologies consist of connecting two or more identical converters in parallel and have the advantages of allowing a reduction in the dimensioning of components, an improvement in power quality, less ripple in the output battery voltage, and facilitating transient filtering, in addition to the best dynamic response. The topology of interleaved DC–DC converters, applied to bidirectional power flow systems, is described and analyzed. The mathematical modeling of the photovoltaic and battery converters is based on the average state-space model applied to the different operating states in continuous conduction mode. The bidirectional converter presents the problem of the nonminimum phase, which reduces the closed-loop bandwidth and makes the dynamic response of the converter slower. In this situation, PID controllers do not work well with load changes, line changes, and parametric uncertainties. Therefore, the main objective of the research is to propose a controller for the three-phase interleaved bidirectional converter by internal control model (IMC). Due to the characteristic of robust control, the IMC in cascade is adopted, with four control loops, three internal current loops, one for each phase of the converter, and an external voltage loop. For comparison purposes, are used Type-II and Type-III controllers, due to their robust control characteristics. The comparison is based on quality parameters, such as reduction of the battery current ripple, and voltage and frequency stability of the microgrid, in the battery charge and discharge modes. The results through simulations in MATLAB/ Simulink suggest the regularity and stability of the three controls, all of which can be considered robust controls for the interleaved converter. The IMC controller demonstrates advantages, such as ease of configuration, depending on a single parameter, the λ of the filter, fast response speed when subjected to reference voltage disturbances, and small overshoot.